2023
DOI: 10.3390/ijms24043777
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytoskeleton Protein 4.1 in Immunotherapy

Abstract: Cytoskeleton protein 4.1 is an essential class of skeletal membrane protein, initially found in red blood cells, and can be classified into four types: 4.1R (red blood cell type), 4.1N (neuronal type), 4.1G (general type), and 4.1B (brain type). As research progressed, it was discovered that cytoskeleton protein 4.1 plays a vital role in cancer as a tumor suppressor. Many studies have also demonstrated that cytoskeleton protein 4.1 acts as a diagnostic and prognostic biomarker for tumors. Moreover, with the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Therefore, Gao et al engineered CAR-T cells with NKG2D and shRNA-4.1R to evaluate its effects in PC [ 70 ]. 4.1R is a cytoskeletal protein that plays a significant role in immunomodulation and cancer development [ 71 ]. It was found that 4.1R deletion in NKG2D CAR-T cells is related to their higher cytotoxicity in vitro against PC cells (SW1990, CAPAN2, and PANC28 cells) in a dose-dependent manner.…”
Section: Car-t Cell Therapy In Pancreatic Cancermentioning
confidence: 99%
“…Therefore, Gao et al engineered CAR-T cells with NKG2D and shRNA-4.1R to evaluate its effects in PC [ 70 ]. 4.1R is a cytoskeletal protein that plays a significant role in immunomodulation and cancer development [ 71 ]. It was found that 4.1R deletion in NKG2D CAR-T cells is related to their higher cytotoxicity in vitro against PC cells (SW1990, CAPAN2, and PANC28 cells) in a dose-dependent manner.…”
Section: Car-t Cell Therapy In Pancreatic Cancermentioning
confidence: 99%